Spiritual Leadership and Job Engagement: The Mediating Role of Emotion Regulation - Huang, Yicong (Frontiers in Psychology, 2022)
Bid data era has bring big challenge for firms in human resource management, especially in employees` emotion. Drawing on emotion regulation and leadership theories, this study investigates the mediating effects of emotion regulation for cognitive reappraisal and expressive suppression in the relationship between spiritual leadership and job engagement. We conducted a field study with 203 full-time employees to test our hypotheses. Results supported the mediating effects of both cognitive reappraisal and expressive suppression in accounting for the relationship between spiritual leadership and job engagement. Our study is among the first to examine whether and why spiritual leadership predicts job engagement. Our study contributes to the literatures on job engagement and emotion regulation.